Strategies in translating culture-specific items in “Dumb Luck” = Các phương pháp dịch thuật ngữ văn hóa trong tác phẩm Số Đỏ - Dương, Mỵ Trinh (2020)
Regarding CSIs’ uniqueness and textual dependence nature, the paper investigated strategies used by Peter Zinoman in rendering CSIs belonging to different culture categories in So Do - an outstanding work in 1930-1945. The novel So Do and its English version translated by Peter Zinoman and Nguyen Nguyet Cam were chosen as subjects of this study. CSIs classification was adapted from Newmark’s theory of 5 culture categories while translation strategies were based on Baker’s translation taxonomy. The 266 CSIs identified in the novel and their translation revealed that only 7 out of 8 strategies were applied and there were substantial gap in their proportions. Translation by paraphrase using related words (36%) and translation by a more neutral/ less expressive word (17%) were the most favorable strategies employed by Peter Zinoman